PERAN PEMETAAN DAN PENETAPAN STAKEHOLDER SEKOLAH DALAM MENINGKATKAN EFEKTIFITAS MANAJEMEN PENDIDIKAN DI SMAN 13 MUARO JAMBI - Coziffya, Meryza; Muspawi, Mohamad; Rahman, K. A.; Ali, Rd. M. (Jurnal Manajemen Pendidikan, 2025)
Stakeholder mapping is the process of identifying, analyzing and visualizing all parties involved in a project or activity, including in an educational context. With proper mapping, schools can understand the roles, interests, influences, and expectations of each stakeholder. This study aims to describe the implementation of stakeholder mapping at SMAN 13 Muaro Jambi as a strategy to improve the quality of education. This research uses qualitative research methods. The results showed that the school has implemented stakeholder mapping formally, systematically, and continuously with an analytical approach through the use of Power-Interest Grid. SMAN 13 Muaro Jambi applied a comprehensive and participatory approach in mapping stakeholders. Stakeholders are classified based on their level of influence and importance to school policies and operations. This research confirms the importance of inter-stakeholder synergy in creating an inclusive, adaptive and competitive education ecosystem. Thus, stakeholder mapping is not only a managerial instrument but also a transformational strategy in achieving holistic and sustainable education.